Design and Early Development of a Novel Cross Axis Wind Turbine. (May 2017) - Muzammil, W.K.; Wong, K.H.; Chong, W.T.; Gwani, M.; Wang, C.T.; Poh, S.C.; Wang, X.H.
Abstract: A novel cross axis wind turbine (CAWT) which comprises of a cross axis blades arrangement was presented and investigated experimentally. The CAWT is a new type of wind turbine that extracts wind energy from airflows coming from the horizontal and vertical directions. The wind turbine consists of three vertical blades and six horizontal blades arranged in a cross axis orientation. Hubs in the middle of the CAWT link the horizontal and vertical blades through connectors to form the CAWT. The study used a 45° deflector to guide the oncoming airflow upward (vertical wind direction). The results from the study showed that the CAWT produced significant improvement in power output and rotational speed performance compared to a conventional straight-bladed vertical axis wind turbine (VAWT), where the CAWT CPmax is 2.5 times higher than the CPmax produced by the VAWT for the same wind speed of 4.5 m/s.